Brain‐Targeted Aggregation‐Induced‐Emission Nanoparticles with Near‐Infrared Imaging at 1550 nm Boosts Orthotopic Glioblastoma Theranostics. Issue 5 (19th December 2021) - Wang, Jiefei; Liu, Yisheng; Morsch, Marco; Lu, Yiqing; Shangguan, Ping; Han, Lulu; Wang, Zhongjie; Chen, Xiaoyu; Song, Chenhui; Liu, Shunjie; Shi, Bingyang; Tang, Ben Zhong
Abstract: A remaining challenge in the treatment of glioblastoma multiforme (GBM) is surmounting the blood–brain barrier (BBB). Such a challenge prevents the development of efficient theranostic approaches that combine reliable diagnosis with targeted therapy. In this study, brain‐targeted near‐infrared IIb (NIR‐IIb) aggregation‐induced‐emission (AIE) nanoparticles are developed via rational design, which involves twisting the planar molecular backbone with steric hindrance. The resulting nanoparticles can balance competing responsiveness demands for radiation‐mediated NIR fluorescence imaging at 1550 nm and non‐radiation NIR photothermal therapy (NIR‐PTT). The brain‐targeting peptide apolipoprotein E peptide (ApoE) is grafted onto these nanoparticles (termed as ApoE‐Ph NPs) to target glioma and promote efficient BBB traversal. A long imaging wavelength 1550 nm band‐pass filter is utilized to monitor the in vivo biodistribution and accumulation of the nanoparticles in a model of orthotopic glioma, which overcomes previous limitations in wavelength range and equipment. The results demonstrate that the ApoE‐Ph NPs have a higher PTT efficiency and significantly enhanced survival of mice bearing orthotopic GBM with moderate irradiation (0.5 W cm −2 ). Collectively, the work highlights the smart design of a brain‐targeted NIR‐II AIE theranostic approach that opens new diagnosis and treatment options in the photonic therapy of GBM. Abstract : The near‐infrared II (NIR‐II)‐imaging‐guided photothermal therapy (PTT) of nanofluorophores is a promising approach for theranostic of orthotopic glioma. Brain‐targeting nanofluorophores featuring novel molecular design of "backbone distortion + molecular rotor" are prepared. They can balance the photon energy flow to achieve advanced NIR‐II imaging at 1550 nm and photo‐to‐heat ratio for PTT in orthotopic‐glioma‐bearing mice.